In vitro Fermentation of Digested Milk Fat Globule Membrane From Ruminant Milk Modulates Piglet Ileal and Caecal Microbiota - Thum, Caroline; Young, Wayne; Montoya, Carlos A.; Roy, Nicole C.; McNabb, Warren C. (Frontiers in Nutrition, 2020)
Lipids in milk are secreted as a triacylglycerol core surrounded by a tri-layer membrane, the milk fat globule membrane (MFGM). This membrane, known to have important roles in the infant brain and intestinal development, is composed of proteins, glycoproteins and complex lipids. We hypothesised that some of the beneficial properties of MFGM are due to its effects on the gastrointestinal microbiota. This study aimed to determine the effect of a commercial phospholipid concentrate (PC) and enriched bovine, caprine and ovine MFGM fractions on ileal and hindgut microbiota in vitro. Digestion of PC and MFGMs was conducted using an in vitro model based on infant gastric and small intestine conditions. The recovered material was then in vitro fermented with ileal and caecal inocula prepared from five piglets fed a commercial formula for 20 days before ileal and caecal digesta were collected. After each fermentation, samples were collected to determine organic acid production and microbiota composition using 16S rRNA sequencing. All substrates, except PC (5%), were primarily fermented by the ileal microbiota (8-14%) (P<0.05). PC and caprine MFGM reduced ileal microbiota alpha diversity compared to ileal inoculum. Caprine MFGM increased and PC reduced the ileal ratio of Firmicutes:Proteobacteria (P < 0.05), respectively, compared to the ileal inoculum. Bovine and ovine MFGMs increased ileal production of acetic, butyric and caproic acids compared to other substrates and reduced the proportions of ileal Proteobacteria (P < 0.0001). There was a limited fermentation of bovine (3%), caprine (2%) and ovine (2%) MFGMs by the caecal microbiota compared to PC (14%). In general, PC and all MFGMs had a reduced effect on caecal microbiota at a phylum level, although MFG source-specific effects were observed at genus level. These indicate that the main effects of the MFGM in the intestinal microbial population appears to occur in the ileum.